IMPLEMENTASI PERENCANAAN KURIKULUM DALAM PENINGKATAN KUALITAS PEMBELAJARAN DI SMP NEGERI 2 MANIANGPAJO - Masauleng; Muhammad Arafah; Nurcaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation of curriculum planning in improving the quality of learning at UPTD SMP Negeri 2 Maniangpajo. This study uses a qualitative approach with a descriptive research type. The data sources in this study consisted of primary and secondary data. Data collection techniques were conducted through interviews, observations, and documentation. Data analysis used the Miles and Huberman interactive analysis model, which included data reduction, data presentation, and conclusion drawing and verification. Data validity was ensured through source triangulation, technique triangulation, and time triangulation techniques. The results of the study indicate that the implementation of curriculum planning in improving the quality of learning is carried out through several stages, namely the analysis of the needs and characteristics of students, the formulation of learning objectives, the selection of student-centered learning strategies and methods, and the evaluation and continuous development of the curriculum. In addition, there are supporting factors that include school leadership, teacher competence and professionalism, the relevance of curriculum planning to student needs, and the availability of facilities and infrastructure The inhibiting factors found include teachers' limited understanding of the curriculum, differences in teacher competence, and high administrative burdens. Thus, the implementation of good curriculum planning can contribute to improving the quality of learning in schools.